2018
DOI: 10.3390/ijms20010118
|View full text |Cite
|
Sign up to set email alerts
|

NAP Family CG5017 Chaperone Pleiotropically Regulates Human AHR Target Genes Expression in Drosophila Testis

Abstract: To study the regulatory mechanism of the Aryl hydrocarbon receptor (AHR), target genes of transcription are necessary for understanding the normal developmental and pathological processes. Here, we examined the effects of human AHR ligands on male fecundity. To induce ectopic human AhR gene expression, we used Drosophila melanogaster transformed with human AhR under the control of a yeast UAS promoter element capable of activation in the two-component UAS-GAL4 system. We found that exogenous AHR ligands decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…84 A study indicated that AHR activation in the gonads could influence the expression of gene networks that control sperm production and may be of importance for fertility. 85 In addition, our study provided new findings that LYC prevented DEHP-induced spermatogenesis disturbance via AHR/ARNT signaling system, which might be the target molecule for future DEHP toxicity and LYC effector mechanism (Figure 8). In summary, our study indicated that LYC was conducive to improve sperm parameters such as reducing the levels of nuclear damage to DNA and deformity rate and increasing the values of sperm motility, number, and density.…”
Section: ■ Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…84 A study indicated that AHR activation in the gonads could influence the expression of gene networks that control sperm production and may be of importance for fertility. 85 In addition, our study provided new findings that LYC prevented DEHP-induced spermatogenesis disturbance via AHR/ARNT signaling system, which might be the target molecule for future DEHP toxicity and LYC effector mechanism (Figure 8). In summary, our study indicated that LYC was conducive to improve sperm parameters such as reducing the levels of nuclear damage to DNA and deformity rate and increasing the values of sperm motility, number, and density.…”
Section: ■ Discussionmentioning
confidence: 70%
“…It has been reported that AHR overexpression was found in Sertoli, Leydig, and spermatid cells of infertile subjects . A study indicated that AHR activation in the gonads could influence the expression of gene networks that control sperm production and may be of importance for fertility . In addition, our study provided new findings that LYC prevented DEHP-induced spermatogenesis disturbance via AHR/ARNT signaling system, which might be the target molecule for future DEHP toxicity and LYC effector mechanism (Figure ).…”
Section: Discussionmentioning
confidence: 99%